2023
DOI: 10.1007/s10967-022-08705-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of Eu and U sorption on cementitious materials in the presence of organic substances

Abstract: A comparative study of the sorption behavior of europium, a chemical analogue of trivalent actinides, and uranium was performed on hydrated cement paste (HCP) CEM I and calcium-silicate-hydrates (CSH) phase. Kinetic experiments proved that Eu sorption is faster than that of U depending on the phase ratio L/S and the sorption material, whereas EDTA has no significant effect. Same conclusions can be made for equilibrium experiments with HCP and U while with Eu EDTA clearly influenced the distribution ratio Rd wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…Especially for Eu(III) and Sm(III), it can be clearly seen that the immobilisation on Circosil ® is the preferred retention mechanism compared to wall adsorption and classic precipitation in the binary system without adsorbent material. In the literature, wall adsorption of Eu(III) [26,44] and U(VI) [44,51] on PP tubes in the presence of C-S-H phases and hydrated cement paste was also investigated. While Tits et al [26] observed wall adsorption <1% for Eu(III), the results gained by Burešová et al [44] and Pointeau et al [51] are similar to this study.…”
Section: Precipitation and Wall Adsorptionmentioning
confidence: 99%
See 3 more Smart Citations
“…Especially for Eu(III) and Sm(III), it can be clearly seen that the immobilisation on Circosil ® is the preferred retention mechanism compared to wall adsorption and classic precipitation in the binary system without adsorbent material. In the literature, wall adsorption of Eu(III) [26,44] and U(VI) [44,51] on PP tubes in the presence of C-S-H phases and hydrated cement paste was also investigated. While Tits et al [26] observed wall adsorption <1% for Eu(III), the results gained by Burešová et al [44] and Pointeau et al [51] are similar to this study.…”
Section: Precipitation and Wall Adsorptionmentioning
confidence: 99%
“…In the literature, wall adsorption of Eu(III) [26,44] and U(VI) [44,51] on PP tubes in the presence of C-S-H phases and hydrated cement paste was also investigated. While Tits et al [26] observed wall adsorption <1% for Eu(III), the results gained by Burešová et al [44] and Pointeau et al [51] are similar to this study. They found only a small amount of U(VI) adsorbed on the wall (<2 or <5%, c(U(VI)) = 4•10 −9 − 7•10 −8 mol•L −1 ).…”
Section: Precipitation and Wall Adsorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…In assessing the long-term safety of radioactive waste repositories, the interaction between radionuclides and cement-based barrier materials is of great interest [6][7][8][9][10]. The interplay is dependent on both the nature of the radionuclides and the type of cement [10][11][12][13][14]. The retention or migration of radionuclides from the disposal facility is related to several factors specific to a cementitious backfill, including a significant pH gradient, temperature, electrolyte composition, presence of organic compounds, redox potential and ionic strength [6,[8][9][10]14].…”
Section: Introductionmentioning
confidence: 99%